Reduction of Overall and Inappropriate Antibiotic Prescribing within a Veterans Affairs Primary Care System through Peer Comparison of Overall Antibiotic Prescribing Rates. (4th October 2017) - Shively, Nathan R; Buehrle, Deanna J; Clancy, Cornelius J; Decker, Brooke K
Abstract: Background: Reducing inappropriate outpatient antibiotic use is an important national goal. A practical intervention with a relatively low barrier to implementation may be peer comparison of overall antibiotic prescribing rates. Methods: Educational sessions were offered to all primary care providers (PCPs) at VA Pittsburgh. Subsequently, PCPs were sent monthly comparisons of their antibiotic prescribing rate, peer rates, and a system target. The intervention period of January–April 2017 was compared with a seasonal baseline of the same months in 2016. A random sample of prescriptions was reviewed for adherence to consensus guidelines. Results: Educational sessions were attended by 50 (68.5%) PCPs. During the baseline period, 1, 498 acute antibiotic prescriptions were written by 65 PCPs caring for 40, 734 patients, compared with 1, 131 prescriptions written by 73 PCPs caring for 41, 185 patients during the intervention period (24.5% decrease, P < 0.0001). Azithromycin use decreased by 43.9% (442 vs. 248 prescriptions, P < 0.0001), and percentage overall decreased from 29.5% to 21.9%, P < 0.0001. Fluoroquinolone use decreased by 52% (148 vs. 71 prescriptions, P < 0.0001), and percentage overall decreased from 9.9% to 6.3%, P = 0.001. Among reviewed cases, inappropriate antibiotic prescribing decreased from 61.4% (62/101) to 40% (48/120), P = 0.002. No significant differences were observed in guideline-discordant agents (20.5% vs. 13.9%, P = 0.7) or guideline-concordant agents given for a guideline-discordant duration (36.8% vs. 37.1%, P = 0.8). Unnecessary antibiotic prescribing rates were numerically lower for upper respiratory infections (76.9% (30/39) vs. 63.8% (30/47), P = 0.2), urinary tract infections (40% (4/10) vs. 6.7% (1/15), P = 0.1), and COPD exacerbations (75% (6/8) vs. 16.7% (1/6), P = 0.1), and significantly lower for skin and soft-tissue infections (50% (9/18) vs. 7.1% (1/14), P = 0.02). Azithromycin and fluoroquinolones were frequently inappropriate in both periods (80.6% (29/36) vs. 70.8% (17/24) and 85.7% (6/7) vs. 75% (6/8), respectively). Conclusion: In a primary care setting, initial education followed by monthly peer comparison of overall antibiotic prescribing rates reduced overall and inappropriate antibiotic prescribing. Disclosures: All authors: No reported disclosures.